(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The revised adaptation activity successfully engaged 5th grade EFL students in learning the past simple tense through a combination of direct instruction and interactive game-based practice. The positive feedback and observed improvements in understanding suggest that such interactive methods are effective and should be incorporated into future lessons.